A percepção dos beneficiários sobre o Programa Bolsa Família no município de Iguatu-CE - Gomes, Maria Claudene Bezerra (2009)
This research was conducted in the municipality of Iguatu-Ceará, in two areas of Baú District (rural) and Santo Antônio district (urban), with the beneficiaries of the Bolsa Família Program (PBF). Seek grants and data to make an analysis on the perception of them through their reports and speeches on the PBF. We understand that poverty is not only not have a fixed income but also their social isolation, lack of work, health care, a decent housing, education and more active participation in political decision making of improvements in their daily lives. The beneficiary is the principal actor, because their testimony and their perceptions have been fruitful, including that it is inserted in the program because it is not a subject, go hungry and face all the adversity caused by recurrent drought in semi-arid region. We propose in the course of this dissertation, discuss topics related to social exclusion, poverty, and public policies that transfer income in subsidies provided to make a link with the object studied.